God’s Ultimate Purpose to His People: To be blessed and to be a blessing - Warouw, Winda Novita (Klabat Theological Review, 2021)
When God called Abraham in Genesis chapter 12:1-3, He blessed Abraham with a promise. The promise of God is fulfilled and as he departs from the land. From this passage, the promise has spiritual aspect and temporal blessing, particularly the latter. God says, “I will bless you.” It is an assurance of the Creator to His creation and through him, the nations will be blessed.  In the context of the local church in Tondano, Indonesia, there are causes that hinder the development of God’s mission such as the false assumption of what mission is, the lack of responsibility in doing the mission, challenges that come from inside and outside, lack of faith, and many others. If they know what the mission of God is as what is written in the Bible, they will realize that they are the people of mission, people who are chosen for a blessing because the mission of God is to bless his creation.  As God selected Abraham as His messenger through whom to communicate the light to the world, he had no doubt and had confidence that the source of blessing was leading him. The local church in Tondano, Indonesia will have the same blessing as what Abraham had before and the servants of God in like manner must go forth to sow.   Keywords: Mission, blessing   References Akin, Daniel L., David P. Nelson, and Peter R. Schemm, eds. A Theology for the Church . Nashville , Tenn: B & H Academic, 2007. Ashford, Bruce. Theology and Practice of Mission: God, the Church, and the Nations . Nashville, Tenn: B&H Publishing Group, 2011. Barnett, Tommy. Multiplication: Unlock the Biblical Factors to Multiply Your Effectiveness in Leadership & Ministry . Lake Mary, FL: Charisma House, 1997. DeYoung, Kevin, and Greg Gilbert. What Is the Mission of the Church? Making Sense of Social Justice, Shalom, and the Great Commission . Wheaton, Ill: Crossway, 2011. Gelder, Craig Van. The Ministry of the Missional Church: A Community Led by the Spirit . Baker Books, 2007. Goheen, Michael W. A Light to the Nations: The Missional Church and the Biblical Story . Grand Rapids, MI: Baker Academic, 2011. Accessed October 17, 2018. http://public.eblib.com/choice/publicfullrecord.aspx?p=3117127. Hale, Tom, and Steve Thorson. Applied OT Bible Commentary. Colorado Springs, CO: David C. Cook, 2012. Accessed October 18, 2018. http://public.eblib.com/choice/publicfullrecord.aspx?p=4067707. Hoke, Steve, and Bill Taylor. Global Mission Handbook: A Guide for Crosscultural Service . Downers Grove, Ill: InterVarsity Press, 2012. Martin, Robin, and Mike Barnett. Discovering the Mission of God: Best Missional Practices for the 21st Century. Westmont: InterVarsity Press, 2012. Accessed October 16, 2018. http://public.eblib.com/choice/publicfullrecord.aspx?p=3316400. Nichol, Francis D. (Ed). Seventh-Day Adventist Bible Commentary . Vol. 1. Hagerstown, MD: Washington, 1953. Patricia King. 31 Decrees of Blessing for Your Life. Place of publication not identified: Broadstreet Publishing Gr, 2016. Plummer, Minnie Knox. Basic Bible Foundations: A Literacy Textbook and Study Guide of Old Testament Events . Author House, 2006. Westermann, Claus. Blessing in the Bible and the Life of the Church . Overtures to Biblical theology 3. Philadelphia: Fortress Press, 1978. Wright, Christopher J. H. Knowing the Holy Spirit through the Old Testament . Downers Grove, Ill: IVP Academic, 2006. Wright, Christopher J. H. Salvation Belongs to Our God: Celebrating the Bible’s Central Story. Carlisle: Langham Creative Projects, 2013. Accessed October 16, 2018. http://public.eblib.com/choice/publicfullrecord.aspx?p=5198257. ———. The Mission of God: Unlocking the Bible’s Grand Narrative. Westmont: InterVarsity Press, 2013. Accessed October 15, 2018. http://public.eblib.com/choice/publicfullrecord.aspx?p=2033595. Yoder, John Howard. Theology of Mission: A Believers Church Perspective . InterVarsity Press, 2014. “Definition of RELATIONAL.” Accessed October 17, 2018. https://www.merriam-webster.com/dictionary/relational. Four Views on the Church’s Mission. Zondervan, 2017.